Characteristics, causes, and outcome of 54 episodes of bloodstream infections in a cohort of HIV patients. Issue 9 (September 2015) - Declercq, Steven; De Munter, Paul; Derdelinckx, Inge; Verhaegen, Jan; Peetermans, Willy E.; Vanderschueren, Steven; Van Wijngaerden, Eric
Abstract: Background: Patients infected with human immunodeficiency virus (HIV) have an increased risk for bloodstream infections (BSIs). Published recent data on characteristics, etiology, and outcome of BSIs in HIV patients in high income countries are scarce. Methods: Blood cultures from 2001 to 2011 from adult HIV patients were retrieved. Blood cultures considered to be contamination based on isolates and clinical context were excluded. Clinical and microbiological characteristics of BSIs and patients were described, those of community-acquired and nosocomial episodes were compared, and risk factors for 6-month mortality were analyzed. Results: We found 54 episodes of true BSI in 46 patients. Demographics were similar to those of the source cohort of all patients followed between 2001 and 2011. In 63% there was prior AIDS, in 91% a CD4 nadir below 200/mm 3, and in 72% a latest CD4 count < 200/mm 3 . In 13% of patients BSI preceded a new HIV diagnosis within 1 week. Main causative microorganisms were coagulase-negative staphylococci (26%), Streptococcus pneumoniae (20%), and Enterococcus spp. (13%). The most frequent diagnoses were pneumonia (28%) and catheter-related BSI (CRBSI) (28%); 56% of episodes were nosocomial. The 1-month mortality rate was 17%, with a cause of death apparently unrelated to the BSI in five of nine episodes. The 6-month mortality was 28%. Factors of co-morbidity or immunodeficiency other than HIV were significantly associated with 6-month mortality. Conclusions: BSIs in HIV-infected patients occur predominantly in patients with advanced HIV infection. Community-acquired bacteremic pneumococcal pneumonia and nosocomial staphylococcal CRBSIs are the main causes. Mortality following BSI is high, and seems to be driven by underlying complicated HIV infection.